From “build back the same” to transformative recovery: enablers and barriers for climate-focused pathways in post-disaster case studies across Europe - Udovyk, Oksana; Soloviy, Vitaliy; Blanes, Jordi Peris; Nahiduzzaman, Kh Md; Özdoğan, Fatma; Maglione, Andrés David; Pennino, Stella (Frontiers in Sustainable Cities, 2025)
Disasters are frequently framed as opportunities for transformative change. Yet in practice, recovery processes often restore unsustainable systems under the guise of resilience or return to normal. This article examines whether, how, and under what conditions post-disaster recovery can catalyze transformative recovery pathways with a focus on climate mitigation and adaptation. Our study presents an interdisciplinary analytical framework that integrates insights from transformative research, sustainability transitions, and resilience thinking, providing a pragmatic heuristic to navigate post-disaster recovery efforts. We apply the framework to four case studies that represent different systems triggered by different disruptions: agriculture in Italy (drought), housing in Türkiye (earthquake), mobility in Spain (flood), and energy in Ukraine (war). Our findings across the cases show that most recovery efforts fall short of reconfiguring the systems in focus, primarily reproducing pre-disaster patterns, with recovery processes commonly characterized by siloed governance, technocratic fixes, and fragmented activities. Still, disasters can also open opportunities for new climate solutions, collaborations, and narratives that can challenge existing regimes and path dependencies. This is possible through addressing the enablers and barriers that cut across different spheres of transformations. Based on the findings, we argue that transformative recovery cannot be enabled purely through risk management, technical adaptation, or return to normal, but must engage with questions of power, meaning, and governance. The study offers researchers a lens to analyze transformation potential across various types of systems and disruptions and provides policymakers and practitioners with insight into the conditions that are important for transformative recovery.